The Role of Instagram Social Media in Increasing the Number of Sales in the Culinary Business Siomay Jodoh - Dian Fitriyana; Azzahra Vanesya; Fitriatunnisa Shabrina; Sudiana Wachyudi; Ety Setiawati (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
Digital marketing has had a long-term impact and made a game changer in the business world. The use of social media has been growing since 2020—the phenomenon of decreasing the number of followers harms sales. Seller is conscious about improving and maintaining their followers on social media to keep running the business well. Purpose to find out the extent of the participation of Instagram social media as a promotional medium to increase the marketing of culinary business products on @siomayjodoh's Instagram accounts. This study used a descriptive qualitative method. Data collection techniques are carried out by observation, interview, and documentation. Data triangulation methods were used to analyze in this study through data reduction, data presentation, drawing, and conclusion. The results showed the use of Instagram social media as an attractive promotional medium with various features that can be used to support the increase in culinary business products in online marketing. This research only collected data on MSME's “Siomay Jodoh